Quantitative approach to skin field cancerization using a nanoencapsulated photodynamic therapy agent: a pilot study - Passos SK; de Souza PE; Soares PK; Eid DR; Primo FL; Tedesco AC; Lacava ZG; Morais PC (Dove Medical Press, 2013)
Simone K Passos,1,2 Paulo EN de Souza,3 Priscila KP Soares,1,3 Danglades RM Eid,1,2 Fernando L Primo,4 Antonio Cláudio Tedesco,4 Zulmira GM Lacava,1 Paulo C Morais3,51University of Brasília, Institute of Biological Sciences, DF, Brazil; 2Foundation for Teaching and Research on Health Sciences, Brasília, DF, Brazil; 3University of Brasília, Institute of Physics, Brasília, DF, Brazil; 4Department of Chemistry, Faculty of Philosophy, Sciences and Letters of Ribeirão Preto, Laboratory of Photobiology and Photomedicine, University of São Paulo, Ribeirão Preto, São Paulo, Brazil; 5Department of Control Science and Engineering, Hua-Zhong University of Science and Technology, Wuham, People's Republic of ChinaBackground: This paper introduces a new nanoformulation of 5-aminolevulinic acid (nano-ALA) as well as a novel quantitative approach towards evaluating field cancerization for actinic keratosis and/or skin photodamage. In this pilot study, we evaluated field cancerization using nano-ALA and methyl aminolevulinate (MAL), the latter being commercialized as Metvix®.Methods and results: Photodynamic therapy was used for the treatment of patients with selected skin lesions, whereas the fluorescence of the corresponding photosensitizer was used to evaluate the time evolution of field cancerization in a quantitative way. Field cancerization was quantified using newly developed color image segmentation software. Using photodynamic therapy as the precancer skin treatment and the approach introduced herein for evaluation of fluorescent area, we found that the half-life of field cancerization reduction was 43.3 days and 34.3 days for nano-ALA and MAL, respectively. We also found that nano-ALA targeted about 45% more skin lesion areas than MAL. Further, we found the mean reduction in area of skin field cancerization was about 10% greater for nano-ALA than for MAL.Conclusion: Although preliminary, our findings indicate that the efficacy of nano-ALA in treating skin field cancerization is higher than that of MAL.Keywords: photodynamic therapy (PDT), nanoemulsion, 5-aminolevulinic acid, actinic keratosis, field cancerization, skin cancer